Public health impact and economic benefits of quadrivalent influenza vaccine in Latin America. Issue 4 (3rd April 2017) - Jamotte, Aurélien; Clay, Emilie; Macabeo, Bérengère; Caicedo, Andrès; Lopez, Juan Guillermo; Bricks, Lucia; Romero Prada, Martín; Marrugo, Rubén; Alfonso, Pamela; Moreno Arévalo, Brechla; Franco, Danilo; Garcia Diaz, Lourdes; et al.
ABSTRACT: Annual trivalent influenza vaccines (TIV) containing 2 A strains and one B lineage have been recommended for the prevention of influenza in most of Latin American countries. However, the circulation of 2 B lineages (Victoria and Yamagata) and difficulties in predicting the predominating lineage have led to the development of quadrivalent influenza vaccines (QIV), including both B lineages. Thus, the objective was to estimate the public health impact and influenza-related costs if QIV would have been used instead of TIV in 3 Latin American countries. We used a static model over the seasons 2010–2014 in Brazil, 2007–2014 in Colombia and 2006–2014 in Panama, focusing on population groups targeted by local vaccination recommendations: young children, adults with risk factors and the elderly. In Brazil, between 2010 and 2014, using QIV instead of TIV would have avoided US 6, 200 per 100, 000 person-years in societal costs, based on 168 influenza cases, 89 consultations, 3.2 hospitalizations and 0.38 deaths per 100, 000 person-years. In Colombia and Panama, these would have ranged from US 1, 000 to 12, 700 (based on 34 cases, 13–25 consultations, 0.6–8.9 hospitalizations and 0.04–1.74 deaths) and from US 3, 000 to 33, 700 (based on 113 cases, 55–82 consultations, 0.5–27.8 hospitalizations and 0.08–6.87 deaths) per 100, 000 person-years, respectively. Overall, the broader protection offered by QIV would have reduced the influenza humanistic and economic burden in the 3 countries. Despite the lack of local data leading to several extrapolations, this study is the first to give quantitative estimates of the potential benefits of QIV in Latin America.